First insight into the Neolithic subsistence economy in the north‐east Iberian Peninsula: paleodietary reconstruction through stable isotopes. Issue 1 (26th August 2016) - Fontanals‐Coll, Maria; Eulàlia Subirà, M.; Díaz‐Zorita Bonilla, Marta; Gibaja, Juan F.
Abstract: Objectives: The study of subsistence strategies among Neolithic communities in north‐east Iberia, late‐fifth to early‐fourth millennia cal BC, enables a more in‐depth study of the activities and behavior of the inhabitants of this region, where paleodiets have been little studied. The objectives of this study are, therefore, to determine the diet and subsistence patterns of those communities and to consider whether any relation existed between their subsistence strategies and environmental, geographic, and/or social factors. Materials and Methods: Bone samples from 25 middle Neolithic human individuals at seven archeological sites and comparative faunal samples were analyzed, and compared with contemporary series in Mediterranean Europe. Carbon and nitrogen isotope ratios (δ 13 C and δ 15 N) of bone collagen were studied to determine the dietary patterns. Results: Dietary habits proved to be similar between communities, apart from some interpopulational variations in subsistence strategies. Their diet was based on C3 terrestrial resources with a major vegetal protein component. Discussion: The reported variations in interpopulational subsistence strategies among the compared Mediterranean societies do not seem to be directly related to the settlement region. Together with archeological data, this indicates the influence of socioeconomic factors in the Neolithic human diet. A general tendency toward a lesser use of aquatic resources is seen in this period in Iberia and the rest of the Mediterranean, as also documented for contemporary communities in the west and north of Europe. The data obtained will be important for further studies of socioeconomic patterns in European Neolithic societies.